2018
DOI: 10.12688/f1000research.16247.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding the physiology of hypoxic sensing by the carotid body

Abstract: Hypoxia resulting from reduced oxygen (O 2) levels in the arterial blood is sensed by the carotid body (CB) and triggers reflex stimulation of breathing and blood pressure to maintain homeostasis. Studies in the past five years provided novel insights into the roles of heme oxygenase-2 (HO-2), a carbon monoxide (CO)-producing enzyme, and NADH dehydrogenase Fe-S protein 2, a subunit of the mitochondrial complex I, in hypoxic sensing by the CB. HO-2 is expressed in type I cells, the primary O2-sensing cells of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Wild-type and genetically-engineered mice are widely used to understand the mechanisms by which hypoxic challenges elicit carotid body-dependent and -independent ventilatory responses (He et al, 2000(He et al, , 2002(He et al, , 2003Kline and Prabhakar, 2000;Pérez-García et al, 2004;Kline et al, 2005;Pichard et al, 2015;Gao et al, 2017;Wang et al, 2017;Ortega-Sáenz et al, 2018;Peng et al, 2018;Prabhakar et al, 2018). The morphology, neurophysiology and neuropharmacology of the mouse CSC-SCG has received considerable investigation over the years (Black et al, 1972;Yokota and Yamauchi, 1974;Banks and Walter, 1975;Inoue, 1975;Lewis and Burton, 1977;Forehand, 1985;Kidd and Heath, 1988;Gibbins, 1991;Kasa et al, 1991;Little and Heath, 1994;Jobling and Gibbins, 1999;El-Fadaly and Kummer, 2003;David et al, 2010;Cadaveira-Mosquera et al, 2012;Pashai et al, 2012;Alberola-Die et al, 2013;Liu and Bean, 2014;Martinez-Pinna et al, 2018;Mitsuoka et al, 2018;Feldman-Goriachnik and Hanani, 2019;Simeone et al, 2019;Rivas-Ramírez et al, 2020).…”
mentioning
confidence: 99%
“…Wild-type and genetically-engineered mice are widely used to understand the mechanisms by which hypoxic challenges elicit carotid body-dependent and -independent ventilatory responses (He et al, 2000(He et al, , 2002(He et al, , 2003Kline and Prabhakar, 2000;Pérez-García et al, 2004;Kline et al, 2005;Pichard et al, 2015;Gao et al, 2017;Wang et al, 2017;Ortega-Sáenz et al, 2018;Peng et al, 2018;Prabhakar et al, 2018). The morphology, neurophysiology and neuropharmacology of the mouse CSC-SCG has received considerable investigation over the years (Black et al, 1972;Yokota and Yamauchi, 1974;Banks and Walter, 1975;Inoue, 1975;Lewis and Burton, 1977;Forehand, 1985;Kidd and Heath, 1988;Gibbins, 1991;Kasa et al, 1991;Little and Heath, 1994;Jobling and Gibbins, 1999;El-Fadaly and Kummer, 2003;David et al, 2010;Cadaveira-Mosquera et al, 2012;Pashai et al, 2012;Alberola-Die et al, 2013;Liu and Bean, 2014;Martinez-Pinna et al, 2018;Mitsuoka et al, 2018;Feldman-Goriachnik and Hanani, 2019;Simeone et al, 2019;Rivas-Ramírez et al, 2020).…”
mentioning
confidence: 99%
“…HO-2 also oxidizes heme to CO and biliverdin, is constitutively expressed in all cells with the promoter responding to glucocorticoids, is a substrate for biliverdin reductase kinase activity, is an oxygen sensor, binds heme to molecules not involved in the catalytic function of the oxygenase, regulates normal cell function, and is important in cellular homeostasis. 24 25 26 27 HO-2 is mainly located in microsomal fractions with HO-1 seen in the microsomal and cytosol fraction. 28 HO-2 activity depends on phosphorylation which is dependent on different protein kinases.…”
Section: P Roduction /R Egulation Of mentioning
confidence: 99%
“…[1][2][3][4][5] Chemosensitive glomus cells within the carotid bodies depolarize in response to decreases in blood pO 2 , increases in blood pCO 2 , and from carbonic anhydrase-catalyzed production of H + ions from increased availability of blood CO 2 . [6][7][8][9][10][11][12][13] Once depolarized, glomus cells release an array of excitatory neurotransmitters [14][15][16][17][18][19][20][21][22][23][24] that trigger action potentials in the nerve terminals of chemoafferents that travel to the nucleus tractus solitarius (NTS) via the carotid sinus nerve (CSN). 6,[8][9][10][11][12] CSN chemoafferent input to the NTS signals a series of downstream cardiorespiratory responses, such as increases in minute ventilation and blood pressure, to restore arterial blood gas homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…[59][60][61][62][63][64][65][66] Wild-type (WT) mice of various strains and genetically-engineered mice are used to investigate mechanisms by which HCC and HXC elicit ventilatory responses that are dependent and independent of the carotid bodies. 20,21,37,[67][68][69][70][71][72][73][74][75][76][77][78][79][80][81] We reported that the ventilatory responses elicited by a HXC were markedly reduced in freely moving adult male C57BL6 mice with bilateral carotid sinus nerve transections (CSNX). 37 Earlier, Izumizaki et al 51 examineded the involvement of the carotid body-CSN in breathing responses to a hyperoxic (100% O 2 )-hypercapnic (5% CO 2 ) gas challenge in urethaneanesthetized adult male C57BL-6CrSlc mice and found that the ventilatory responses were markedly reduced after bilateral CSNX.…”
Section: Introductionmentioning
confidence: 99%